Technological management of oil companies in face of global challenges - A. E. Miller; L. M. Davidenko (Омский научный вестник: Серия "Общество. История. Современность")
The paper describes the current state of integrated economic structures of the oil and gas sector in the face of falling demand for oil and oil products, intensified by the difficult epidemiological situation in regional consumer markets. Methodological approaches to the management of technological resources of large industrial facilities in the restructuring of the management system are justified. Attention is paid to the expansion of the functions of «remote access». The accumulated experience of growing technological potential through the technological integration of digital platforms is summarized. The importance of the effectiveness of innovation and technology activities of companies with the help of centers of responsibility zones, signals of weak activity of multichannel communication at all levels of management is emphasized. Existing programs for technological modernization of production facilities should adapt to fluctuations in supply and demand in the petrochemical products market. Factors of increasing competitiveness include technological superiority, the availability of sources of investment resources, as well as the improvement of technological management of industrial companies, based on a motivational approach to increasing the adaptability of human capital to environmental challenges